The textual dialogue between Aulularia by Plauto and El avaro by Molièr - González, Daniela Soledad (2018)
This article is based on the notion of transtextuality as an essential feature of any literary work. Two comedies are analyzed comparatively: Aulularia, by Plautus and The greedy man, by Molière. The analysis is hermeneutical and stylistic. It is observed that are similar comedies because they have the greedy man as a main character and target of their social critic. In addition, formal similarities between comedies are numerous: high dramatic tension, customs and beliefs exibition, living and stylized language, type characters, beatings, comic situations, criticism of certain occupations/professions and a predominant role of slaves. Both books also take up classic antiquity: Plautus, the Hellenic one; Molière, Greco-Roman one. Finally, both comedies subject is the same. Given these similarities and taking into account Genette's theory in Palimpsestos, it is concluded that the relationship established between comedies is indirect hypertextuality or imitation. In particular, a kind of imitation called forgerie. The reason for the existence of such relationship between comedies is primarily ancient world's arquetipicity, which suits with the fact that Molière belonged to the literary movement known as Neoclassicism.